A influência da temperatura na secagem forçada da matéria-prima cerâmica da Formação Corumbataí na região do Polo de Santa Gertrudes (SP) - Azzi, Andrezza de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The ceramic tiles production in Brazil reached almost 1 billion m² in 2013. More than 60% of these tiles were produced in the Ceramic District of Santa Gertrudes (CDSG). The main advantage of ceramic industries from Santa Gertrudes district is an application of the dry grinding process, which is much more profitable than the wet grinding process, used worldwide. The dry grinding process accounted for 73 % of tiles production in the CDSG in 2013. For the dry route of tiles production, only rocks from Corumbataí Fm. in the region are used, which decreases costs for raw material transportation. On the other hand, the booming ceramic industry in the Santa Gertrudes district has caused air pollution and river silting due to large amount of dust generated by drying and transportation the raw material. Ceramic companies need to replace their current beneficiation areas by industrial dryers. However, the batch whose raw materials were drying forced has produced tiles that break or crack during the industrial process. Three types of raw materials, D (slightly weathered), I (weathered) and M (highly weathered) were examined in the present study in order to better understand the behavior of clays during the drying process. Clay minerals characterization were made using qualitative and quantitative XRD, petrographic studies, infrared spectroscopy (FTIR), thermo gravimetric analysis (DTA-TG-DTG), SEM e TEM. Quantitative XRD analysis showed that D, I and M contain 53, 63 and 64 wt.% of clay minerals, respectively. Illite and smectite are the main minerals, probably with a small amount of mixed-layered illite-smectite. Sample M contains also kaolinite that according to XRD analysis may be accompanied with mixed-layered kaolinite-smectite. Thermal experiment was realized in different temperatures (100°C, 200°C and 300°C) for fraction < 2 μm. Air dried XRD pattern indicated smectite collapses over 100°C. After 200°C and 300°C the ethylene glycol...

A produção de revestimentos cerâmicos no Brasil atingiu quase 1 bilhão de m² em 2013. Mais de 60% dos produtos foram produzidos no Polo Cerâmico de Santa Gertrudes (PSG). Neste polo, 73 % dos revestimentos cerâmicos foram fabricados pelo processo via seca tradicional. Na fabricação via seca do PSG são utilizadas apenas rochas da Formação Corumbataí extraídas da região, o que diminui os custos com o transporte da matéria-prima. Por outro lado, nesta região, a poluição atmosférica e o assoreamento dos rios são relacionados em parte à grande quantidade de poeira gerada nas etapas de secagem da matéria-prima cerâmica. Nesse sentido, as empresas do PSG necessitam substituir seus atuais pátios de secagens por secadores industriais ou quaisquer alternativas que não causem a dissipação de particulados no meio ambiente. No entanto, as matérias-primas que têm sido submetidas à secagem forçada têm produzido peças que quebram ou trincam durante o processo industrial. A fim de entender o comportamento das argilas expostas à secagem forçada, três tipos de matérias-primas utilizadas pelas indústrias cerâmicas, D (dura), I (intermediária) e M (mole) foram selecionadas para o presente estudo. A caracterização dos argilominerais foram feitas utilizando difração de raios X, petrografia, análise por infravermelho, análise termogravimétrica, MEV e MET. A análise quantitativa por difração de raios X mostrou que D, I e M contêm respectivamente 53, 63 e 64 % de argilominerais. Illita e esmectita são os principais argilominerais, provavelmente com uma pequena quantidade de interestratificados illita-esmectita. A amostra I e M contêm caulinita, que também se apresenta como interestratificados caulinita-esmectita. Tratamentos térmicos foram realizados em diferentes temperaturas (100°C, 200°C e 300°C) nas amostras D, I e M na fração < 2 μm. O difratograma após a secagem forçada indica um progressivo colapso das...
Keywords: Materials science; Ciência dos materiais; Ceramica; Processos de fabricação; Geologia; Argila; Argila - Secagem; Ceramica - Industria; Santa Gertrudes (SP)